How Tax Payer Awareness Mediates Fiscal Services and Supervision Towards Tax Compliance: Post-Organization Study at Cilegon Tax Service Office - Saeroji, Oji; Patiro, Shine Pintor Siolemba; Meliala, Janita S. (PINISI Discretion Review, 2024)
Compliance of taxpayers is a crucial component in the implementation of self-assessment in tax collection in Indonesia. The Directorate General of Taxes has undergone organizational changes, particularly in tax service and supervision, as an effort to enhance tax payment order. The objective of this research is to analyze the role of tax service and supervision in explaining and predicting taxpayer compliance, with taxpayer awareness as a mediating variable. The study population consists of strategic taxpayers at the Primary Tax Service Office in Cilegon, totaling 529, with a sample size of 98 respondents. The independent variables in this study are tax service and tax supervision, while the dependent variable is taxpayer compliance, and taxpayer awareness serves as a mediating variable. Variable measurements were conducted using a questionnaire. Data analysis was performed using the structural equation modeling partial least squares (SEM PLS) software, yielding results that tax service and tax supervision significantly influence taxpayer compliance. Tax service and tax supervision also significantly affect taxpayer awareness. Taxpayer awareness, in turn, significantly influences taxpayer compliance. This research is expected to provide managerial implications for the implementation of organizational changes, especially in the functions of tax service and supervision.